Effect of multiple firing and silica deposition on the zirconia-porcelain interfacial bond strength - Cavalcanti Queiroz, Jose Renato [UNESP]; Benetti, Paula [UNESP]; Massi, Marcos; Nogueira Junior, Lafayette [UNESP]; Della Bona, Alvaro (Elsevier B.V., 2012)
Objectives. To test the hypothesis that multiple firing and silica deposition on the zirconia surface influence the bond strength to porcelain.Materials and methods. Specimens were cut from yttria-stabilized zirconia blocks and sintered. Half of the specimens (group S) were silica coated (physical vapor deposition (PVD)) via reactive magnetron sputtering before porcelain veneering. The remaining specimens (group N) had no treatment before veneering. The contact angle before and after silica deposition was measured. Porcelain was applied on all specimens and submitted to two (N2 and S2) or three firing cycles (N3 and S3). The resulting porcelain-zirconia blocks were sectioned to obtain bar-shaped specimens with 1 mm(2) of cross-sectional area. Specimens were attached to a universal testing machine and tested in tension until fracture. Fractured surfaces were examined using optical microscopy. Data were statistically analyzed using two-way ANOVA, Tukey's test (alpha = 0.05) and Weibull analysis.Results. Specimens submitted to three firing cycles (N3 and S3) showed higher mean bond strength values than specimens fired twice (N2 and S2). Mean contact angle was lower for specimens with silica layer, but it had no effect on bond strength. Most fractures initiated at porcelain-zirconia interface and propagated through the porcelain.Significance. The molecular deposition of silica on the zirconia surface had no influence on bond strength to porcelain, while the number of porcelain firing cycles significantly affected the bond strength of the ceramic system, partially accepting the study hypothesis. Yet, the Weibull modulus values of S groups were significantly greater than the m values of N groups. (C) 2012 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Bond strength; Firing; Plasma; Porcelain; Zirconia